Agronomic performance of curly lettuce seedlings from mill compost substrate under organic cropping system - Luiz Fernando de Sousa Antunes; Adelson Paulo Araújo; Maria Elizabeth Fernandes Correia; Norma Gouvêa Rumjanek; José Guilherme Marinho Guerra (International Journal of Recycling of Organic Waste in Agriculture)
Purpose: Millicompost is an organic substrate generated by the activity of millipedes (diplopods) with high potential for seedling production. This work aimed to evaluate the performance of green curly lettuce (Lactuca sativa L.) using seedlings produced with millicompost, at different levels of nitrogen (N) fertilization at seedling transplant, in an organic production system. Method: A field experiment was carried out in Seropédica, Rio de Janeiro State, Brazil, in a 2x4 factorial design with four replications, combining seedlings produced with two substrates (millicompost or Biomix® - used as reference) and four levels of N fertilization with castor cake (0, 50, 100 and 200 kg N ha-1) at seedling transplant. Plants were sampled weekly, and lettuce production was evaluated at 42 days after transplant. Results: Seedlings produced with millicompost had root dry mass, plant height, and number of leaves higher than those produced with commercial substrate. At levels 0 and 50 kg N ha-1, lettuce plants originating from seedlings produced with millicompost showed a higher growth rate than those with the commercial substrates, between 35 and 42 days after transplant. Fresh commercial weight, head diameter, and number of leaves of lettuce plants increased linearly as applied N levels increased. These traits were superior in plants from seedlings produced with millicompost than with commercial substrate. Conclusion: The millicompost provided seedlings of improved quality that increased the growth and yield of lettuce plants in the field at different levels of N fertilization.